Pre- and post-pandemic risk perceptions and worries - Wolff, Katharina; Larsen, Svein (Frontiers in Psychology, 2024)
Introduction The present study is a cross-sectional investigation of worry and risk perceptions regarding various hazards and destinations, measured before, during, and after the COVID-19 pandemic. Methods Questionnaire data were collected from tourists in Norway during the summer seasons of 2012 (N = 2,669), 2019 (N = 1,666), and 2022 (N = 956), and from a representative sample of Norwegians in 2020 (N = 1,003). Results The results show a general decline in the level of worry and risk perceptions post-pandemic compared to those pre-pandemic, with the exception of infectious diseases, whose perceived risk slightly increased in 2022. Conclusion The results highlight the importance of employing cross-sectional or longitudinal data to investigate changes in risk perceptions over time. The findings also indicate that pessimistic predictions of a continued decline in tourism appear to be unwarranted.